THE RELATIONSHIP BETWEEN SELF-REGULATION AND ANXIETY IN FACING THE WORLD OF WORK IN FINAL YEAR STUDENTS IN THE SIDOARJO AREA - Septiansyah, Danang Aditya Pratama; Widyastuti, Widyastuti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to investigate the relationship between self-regulation and anxiety among final-year students in Sidoarjo as they prepare to enter the increasingly competitive job market. Method: Using a quantitative approach with purposive sampling, the research involved 204 final-year students who met specific inclusion criteria. Data were collected through validated instruments: a self-regulation scale (α = 0.975) and an anxiety scale (α = 0.977). The Pearson product-moment correlation analysis was conducted using SPSS version 25. Results: The analysis revealed a strong negative correlation between self-regulation and anxiety, with a correlation coefficient of -0.727 and a significance level of 0.000. The coefficient of determination (R²) was 0.529, indicating that self-regulation contributes to 53% of the variance in anxiety levels. Novelty: This study contributes to the limited empirical evidence in the Indonesian context, specifically in Sidoarjo, highlighting the psychological readiness of final-year students in relation to workforce entry. It emphasizes the need for educational institutions to support students’ self-regulation development as a preventive strategy to reduce anxiety and improve career preparedness.